The multimodality of reading poetry and its creative writing in the classroom - Sierpe, Erick Cavalcante; Martinelle, Martina; Martinelli Filho, Nelson (The ESPecialist, 2025)
The didactic sequence presented in this article sought to expose students to as many poems as possible, emphasizing from the beginning the perspective of textual production, with the general objectives of stimulating appreciation for the textual genre of poem, developing the student's aesthetic sensitivity, and improving the ability to write original poetry. The texts discussed ranged from sonnets to slams, in order not to restrict the debate to aspects of written language, nor to aspects of a single tradition. The sequence was aimed at 9th grade classes in Elementary School and 2nd grade in High School, so that each teacher adapted it to the particular demands of the respective stage. In detail, creative writing guidelines were given to students so that they could write their own poems with awareness and more autonomy in relation to the plurality of subjects, forms, and modalities. The methodology used was the didactic sequence of Dolz, J.; Noverraz, M.; Schneuwly, B., (2004, p. 96). As a theoretical framework, we approached studies by Antonio Candido (2004), regarding the importance of literature for human beings; Angela Paiva Dionisio (2007) (2011), when addressing relevant aspects of multimodality in the classroom; and both Luiz Antonio de Assis Brasil (2015) and María Teresa Andruetto (2012), in the approach to creative writing; Neide Luzia de Rezende (2018), regarding the importance of reading and writing, Angela Kleiman (2009), Alba Maria Perfeito (2002) and Adriana Pastorello Buim Arena (2009) and Guilherme Rocha Duran (2009), on the understanding of the associations of author and reader and the interactionist perspective. At the end of the process, it was observed that the most participatory students in the delivery of authorial poems occurred in Elementary School, as well as in orality in dialogue with the texts of the classes.